2021
DOI: 10.1136/annrheumdis-2021-eular.2211
|View full text |Cite
|
Sign up to set email alerts
|

Pos0298 underserved Populations Identify Barriers and Propose Solutions for Self-Managing Arthritis and Chronic Conditions

Abstract: Background:Underserved populations, such as ethnic minorities, low-income adults, and Indigenous people living with arthritis are more likely to have lower health literacy, higher rates of multi-morbidity, and face challenges in accessing care1-3. Self-management support (SMS) can help to mitigate the impacts of living with arthritis4. However, we require a more in-depth understanding of the daily barriers underserved communities face in living with arthritis in order to develop effective SMS that can meaningf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Methods: A team of researchers from several universities, nurse practitioners, physicians, policy makers, an arthritis consumer-patient leader and our community partners (Multi-lingual Orientation Service Association for Immigrant Communities and the Portland Hotel Society Community Services Society) engaged in a Community-based Participatory and Concept Mapping (CM) study [5][6][7] where participants from underserved communities identified major barriers they face in managing arthritis, agreed on key themes that emerged, and determined priorities for actions. This involved three key CM activities: 1) brainstorming ideas; 2) sorting and rating ideas; and 3) analyzing and interpreting concept maps 8 . Data was collected through face-to-face interviews and prioritized and interpreted in workshop settings.…”
Section: Referencesmentioning
confidence: 99%
“…Methods: A team of researchers from several universities, nurse practitioners, physicians, policy makers, an arthritis consumer-patient leader and our community partners (Multi-lingual Orientation Service Association for Immigrant Communities and the Portland Hotel Society Community Services Society) engaged in a Community-based Participatory and Concept Mapping (CM) study [5][6][7] where participants from underserved communities identified major barriers they face in managing arthritis, agreed on key themes that emerged, and determined priorities for actions. This involved three key CM activities: 1) brainstorming ideas; 2) sorting and rating ideas; and 3) analyzing and interpreting concept maps 8 . Data was collected through face-to-face interviews and prioritized and interpreted in workshop settings.…”
Section: Referencesmentioning
confidence: 99%